Fit for Diversity: A Staff-Driven Organizational Development Process Based on the Organizational Health Literacy Responsiveness Framework - Anna Aaby; Sanne Palner; Helle Terkildsen Maindal (SLACK Incorporated, 2020)
Working toward equity in health requires attention to local needs. Organizational health literacy responsiveness is defined as the way health information and resources are made available and accessible to people. This case study aims to investigate the feasibility of the the Organizational Health Literacy Responsiveness (Org-HLR) process in developing a health literacy strategy in a Danish municipal rehabilitation unit. The Org-HLR investigates organizational health literacy responsiveness within six domains: (1) leadership and culture; (2) systems, processes, and policies; (3) access to services and programs; (4) community engagement and partnerships; (5) communication practices and standards; and (6) workforce. During three workshops, we applied the appropriate tools to allow staff and management to reflect upon and self-assess local organizational health literacy needs and develop and prioritize ideas for improvement. During the Org-HLR self-assessment, 62 ideas for improvement were identified. After prioritization, the unit produced an action plan with 11 items to develop health literacy responsiveness. The co-creational strategy ensured broad participation, which may increase the likelihood of successful implementation. To become health literacy responsive, organizations need to develop local strategies. This study confirmed the Org-HLR as a feasible approach to identify organizational health literacy needs and to guide organizational health literacy improvements.